Temporal shift in task factor influence across the stretch reflex - Frida Torell; Robin Rohlén; Michael Dimitriou (PLoS ONE, 2026)
Mechanical perturbations applied to the arm can elicit reflexive actions. These rapid corrective responses include the stretch reflex, which consists of different components: the short-latency reflex (SLR) and the early and late long-latency reflex (LLR). In this study, we examine how different task factors dynamically influence these reflex components in the context of a specific delayed-reach paradigm. Using multiple linear regression (MLR), we analysed electromyographic (EMG) activity from seven muscles actuating the right arm to examine the effects of mechanical load, preparatory delay, perturbation and target direction, on reflex responses, as well as two-factor interactions. The MLR analysis shows that our delayed-reach tasks engaged shoulder girdle muscles in a task-dependent manner, whereas the biceps and triceps primarily acted as stabilizing muscles, with rapid responses triggered regardless of perturbation direction. Specifically, our analyses show that the earliest corrective response, the SLR, exhibited some task-dependent modulation particularly in muscles of the shoulder girdle, although background (pre-)loading decreased this modulation. The SLR was primarily influenced by the main factors Load and Perturbation , along with the interaction Load × Perturbation . Perturbations aligned with the load direction were associated with increased EMG activity across all examined muscles. While there was a small but significant effect of load during the early LLR, this effect diminished by the late LLR epoch. Task-dependent modulation was most pronounced at the late LLR epoch, suggesting greater top-down modulation of this reflex component. In particular, the late LLR was shaped by the factors Perturbation and Target , as well as the interaction Perturbation × Target . Targets and perturbations in opposite directions resulted in heightened EMG activity, and shoulder muscles exhibited stronger LLR responses for targets located farther along the muscle shortening direction. Our results complement and expand on previous findings concerning stretch reflex modulation and help guide the design of future studies.